DAYA SAING MADU KELULUT LOMBOK, PROVINSI NUSA TENGGARA BARAT (The Competitiveness of Honey Kelulut Lombok, West Nusa Tenggara Province) - yumantoko Yumantoko; Ramdiawan Ramdiawan (Journal Penelitian Kehutanan FALOAK, 2021)
AbstractKelulut honey is one of the prioritized NTFPs in West Nusa Tenggara Province regarding its economic potential for the communities. In addition, related stakeholders have provided supports such as training, incentives, forest area management, industrialization and marketing. However, these supporst do not effectively encourage many community members to pay serious attention in cultivating kelulut bees. It can be seen from the many abandoned stup (bee box) from aid and the apathy due to the doubts about the economic potential of this business. This study aims to describe the advantages of kelulut honey cultivation in Lombok from a financial perspective. The study was conducted in two districts, West Lombok and North Lombok. Primary data was collected through interviews using a questionnaire with a purposive technique. The data was analyzed using the Policy Analysis Matrix (PAM). The results showed that kelulut honey from Lombok has competitive and comparative advantages. However, government policies remain less affected by the increasing income of bee farmers. So, efforts from stakeholders are still required to intervene in the business to attract more people in cultivating kelulut bees.AbstrakMadu kelulut merupakan salah satu HHBK unggulan di Provinsi Nusa Tenggara Barat karena memberi banyak manfaat untuk masyarakat. Para pihak telah memberi intervensi antara lain dengan pelatihan, insentif modal, penataan kawasan, industrialisasi, pemasaran, dan lain sebagainya. Namun hal itu kurang mendorong masyarakat untuk mengusahakan, terlihat dari stup (kotak lebah) bantuan banyak terbengkalai dan sikap apatis karena ragu dengan potensi ekonomi madu kelulut. Penelitian ini bertujuan untuk melihat keunggulan pengusahaan madu kelulut di Lombok dilihat dari sisi finansial. Penelitian dilakukan di dua kabupaten yaitu Lombok Barat dan Lombok Utara. Data primer diperoleh lewat wawancara menggunakan kuesioner dengan teknik purposive sampling. Data selanjutnya diolah menggunakan Policy Analisis Matrix (PAM). Hasilnya menunjukkan bahwa madu kelulut dari Lombok  memiliki  keunggulan  kompetitif  dan  komparatif. Namun kebijakan pemerintah belum cukup banyak memengaruhi peningkatan pendapatan petani sehingga masih diperlukan usaha dari para pihak dalam mengintervensi pengusahaan agar menarik lebih banyak lagi masyarakat dalam membudidayakan lebah kelulut.